Q. 105.0( 2 Votes )

# prove that:

, where a= ax – by and β=ay+bx.

Answer :

Given:-

Take

LHS

=

We know that, Formula

Thus,

=

=

=

Formula used:- a^{2} + b^{2} + 2ab = (a+b)^{2}

=

=

As given

a= ax–by and β= ay+bx

Thus,

= RHS

So,

Hence Proved

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Inverse Trigonometric Functions - 0161 mins

Inverse Trigonometric Functions - 0242 mins

Inverse Trigonometric Functions - 0339 mins

Inverse Trigonometric Functions - 0438 mins

Properties of Inverse Trigonomteric Functions35 mins

Interactive Quiz | Graphs of inverse Trigo functions41 mins

Questions Practice of Inverse trigonometric Functions30 mins

Its Quiz Time Now !! : Some Properties of Inverse Trigonometric Functions37 mins

Interactive Quiz | Graphs of inverse trigo functions39 mins

Graphs of inverse trigo functions48 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Prove the following:

**OR**

Prove the following:

Mathematics - Board Papers

Solve the following equation for x :

Mathematics - Board Papers